Analogues of Josephson junctions and black hole event horizons in atomic Bose–Einstein condensates - Yakimenko, A.I.; Matsyshyn, O.I.; Oliinyk, A.O.; Biloshytskyi, V.M.; Chelpanova, O.G.; Vilchynskii, S.I. (Физика низких температур, 2018)
We study dynamical processes in coherently coupled atomic Bose–Einstein condensates. Josephson effects in
ring-shaped and dumbbell geometries are theoretically investigated. Conditions for observation of the Josephson
effect are revealed. We found that multicharged persistent current in toroidal condensate can be robust even for
supersonic atomic flow. In numerical simulations the acoustic analogues of event horizon in quantized superflow
were observed. These theoretical finding open perspectives for investigation of Bose Josephson junctions and
quantum aspects of acoustic analogue of Hawking radiation in existing experimental setups. Вивчено динамічні процеси у когерентно зв’язаному
атомному конденсаті Бозе–Ейнштейна. Теоретично досліджено джозефсонівські елементи в кільцеподібних та гантелеподібних геометріях. Виявлено умови спостереження ефекту
Джозефсона. Визначено, що багатозарядний постійний струм в
тороїдному конденсаті може бути стійким навіть для надзвукового потоку атомів. У числових розрахунках спостерігалися
акустичні аналоги горизонтів подій в квантованих надпотоках.
Ці теоретичні знахідки відкривають перспективи для дослідження бозе-джозефсонівських переходів та квантових аспектів
акустичного аналога випромінювання Хокінга в існуючих
експериментальних пристроях. Изучены динамические процессы в когерентно связанном
атомном конденсате Бозе–Эйнштейна. Теоретически исследованы джозефсоновские элементы в кольцеобразных и гантелеобразных геометриях. Выявлены условия наблюдения эффекта
Джозефсона. Обнаружено, что многозарядный постоянный ток
в тороидальном конденсате может быть устойчивым даже для
сверхзвукового потока атомов. В численных расчетах наблюдались акустические аналоги горизонтов событий в квантованных суперпотоках. Эти теоретические находки открывают перспективы для исследования бозе-джозефсоновских
переходов и квантовых аспектов акустического аналога излучения Хокинга в существующих экспериментальных установках.